Cadmium isotope fractionation in seawater - A signature of biological activity - Ripperger, S; Rehkaemper, M; Porcelli, D; Halliday, A (2007)
Investigations of cadmium isotope variations in the oceans may provide new insights into the factors that control the marine distribution and cycling of this element. Here we present the results of Cd isotope and concentration analyses for 22 seawater samples from the Atlantic, Southern, Pacific, and Arctic Oceans. The results reveal, for the first time, large and well resolved Cd isotope fractionations in the marine environment. The majority of the seawater samples display an inverse relationship between dissolved Cd contents and isotope compositions, which range from ε114/110Cd ≈ + 3 ± 0.5 for Cd-rich waters (0.8-1.0 nmol/kg) to ε114/110Cd ≈ 38 ± 6 for surface water with a Cd concentration of only 0.003 nmol/kg (all ε114/110Cd data are reported relative to the JMC Cd Münster standard). This suggests that the Cd isotope variations reflect kinetic isotope effects that are generated during closed system uptake of dissolved seawater Cd by phytoplankton. A few samples do not follow this trend, as they exhibit extremely low Cd contents (< 0.008 nmol/kg) and nearly un-fractionated Cd isotope compositions. Such complexities, which are not revealed by concentration data alone, require that the Cd distribution at the respective sites was affected by additional processes, such as water mass mixing, atmospheric inputs of Cd and/or adsorption. Uniform isotope compositions of ε114/110Cd = + 3.3 ± 0.5 (1 S.D.) were determined for seawater from ≥ 900 m depth, despite of Cd concentrations that display the expected increase along the global deep-water pathway from the Atlantic (∼ 0.3 nmol/kg) to the Pacific Ocean (∼ 0.9 nmol/kg). This indicates that the biomass, which is remineralized in the deeper ocean, is also characterized by a very constant Cd isotope composition. This observation is in accord with the interpretation that the Cd distribution in surface waters is primarily governed by Rayleigh fractionation during near-quantitative uptake of dissolved seawater Cd. © 2007 Elsevier B.V. All rights reserved.